Impact of clinical domains other than arthritis on composite outcomes in psoriatic arthritis: comparison of treatment effects in the SEAM-PsA trial - Helliwell, PS; Mease, PJ; Kavanaugh, A; Coates, LC; Ogdie, A; Deodhar, A; Strand, V; Kricorian, G; Liu, L; Collier, D; Gladman, DD (BMJ Publishing Group, 2022)
Objective We used the Study of Etanercept And Methotrexate in Combination or as Monotherapy in Subjects with Psoriatic Arthritis (SEAM-PsA) data set to examine the impact of presence of enthesitis, dactylitis, nail disease and/or psoriasis on treatment response in patients with early psoriatic arthritis (PsA).